Political Ecology Evaluation of Waste Management Policy in Banjarmasin City - Hendra, Hendra; Arisanty, Deasy (CV. Science Tech Group, 2025)
Rapid urbanization in Banjarmasin City has intensified domestic waste management challenges, posing a significant obstacle to achieving Sustainable Development Goals (SDGs), particularly those related to urban environmental governance. Despite the enactment of Regional Regulation No. 21/2011 promoting the 3R (Reduce, Reuse, Recycle) principles, its implementation remains fragmented and has failed to engage comprehensive community participation. This study adopts a political ecology framework to critically assess the effectiveness of the policy, emphasizing structural barriers such as institutional fragmentation, limited technological adoption, and imbalanced stakeholder power relations. A qualitative case study approach involved in-depth interviews with key stakeholders, document analysis, and field observations. Thematic analysis and triangulation methods were used to validate findings. Results indicate Banjarmasin's waste governance remains largely technocratic and top-down, with inadequate grassroots integration and weak inter-agency coordination. Technological innovations such as digital monitoring and Waste-to-Energy solutions are notably absent, further limiting policy outcomes. This study highlights the urgency of reforming local waste governance through participatory, equitable, and technologically adaptive strategies, particularly for medium-sized cities in the Global South.